Hidden Symmetries of M-Theory and Its Dynamical Realization - Nurmagambetov, A.J. (Symmetry, Integrability and Geometry: Methods and Applications, 2008)
We discuss hidden symmetries of M-theory, its feedback on the construction of the M-theory effective action, and a response of the effective action when locality is preserved. In particular, the locality of special symmetries of the duality-symmetric linearized gravity constraints the index structure of the dual to graviton field in the same manner as it is required to separate the levels 0 and 1 generators subalgebra from the infinite-dimensional hidden symmetry algebra of gravitational theory. This conclusion fails once matter fields are taken into account and we give arguments for that. We end up outlining current problems and development perspectives.